Preparation method of injectable self-healing hydrogel dressing as well as product and application of injectable self-healing hydrogel dressing
By combining the copper-protocatechaldehyde complex CuPA with methacrylylated gelatin GelMA, an injectable self-healing hydrogel dressing was prepared, which solved the problem of difficulty in healing in diabetic wounds, and achieved various functions such as tissue adhesion, hemostasis, antibacterial, antioxidant, anti-inflammatory and pro-angiogenesis, significantly accelerated wound repair.
Patent Information
- Application Number
- CN202411749897.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
High glucose and high oxidative stress levels in diabetic wounds hinder healing and are often accompanied by bacterial infections, resulting in chronic and difficult-to-heal wounds. Existing dressings are difficult to effectively promote repair.
The copper-protocatechaldehyde complex CuPA is used to combine with methacrylylated gelatin GelMA, and polymerization is initiated by free radicals and dynamic Schiff alkaline bond crosslinking to prepare an injectable self-healing hydrogel dressing, which has various functions such as tissue adhesion, hemostasis, antibacterial, antioxidant, anti-inflammatory and pro-angiogenicity.
This hydrogel dressing can effectively promote the healing of diabetic wounds, achieve a variety of biological activities through sustained release of CuPA complexes, improve the wound microenvironment, and significantly accelerate the wound repair process.
Smart Images

Figure CN119746140A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical dressings, and in particular relates to a preparation method of an injectable self-healing hydrogel dressing and a product and application thereof. Background Art
[0002] Diabetic wounds are one of the most serious chronic complications of diabetic patients. The high glucose and high oxidative stress levels in the wound microenvironment seriously hinder the healing of diabetic wounds, and are often accompanied by bacterial infection, which triggers the formation of biofilms, causing diabetic wounds to develop into chronic and difficult-to-heal wounds, greatly prolonging the wound repair process and exacerbating the patient's pain. Therefore, the complex environment of diabetic wounds places high demands on new dressings used to promote diabetic wound repair.
[0003] As a type of three-dimensional network structure material with a high water content (up to 99%), hydrogel is very similar to natural tissue and has good tissue exudate absorption, moisturizing and gas exchange capabilities. Through appropriate polymer material selection and functional modification, hydrogel materials can be endowed with a variety of excellent properties such as tissue adhesion, hemostasis, antibacterial, and injectable. Furthermore, they can be used as delivery carriers for drug molecules, cytokines, nanomaterials, and therapeutic stem cells. Through conditional responsive release, they can achieve spatiotemporal regulation of tissue microenvironment and create a more favorable local environment for tissue repair. Cu 2+ It can effectively inhibit and kill a variety of pathogenic microorganisms (such as Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, etc.) by combining with sulfhydryl groups, changing the permeability of bacterial cell membranes, and producing reactive oxygen. 2+ It is closely related to fibroblast growth factor (FGF) and has a synergistic stimulatory effect on angiogenesis. 2+ It can also directly promote the production of vascular endothelial growth factor (VEGF), increase the expression of hypoxia-inducible factor 1α (HIF-1α) and inhibit its degradation, and promote angiogenesis. Polyphenol molecules (such as tannic acid, protocatechuic aldehyde, etc.) can promote the transformation of macrophages from M1 to M2 in the middle and late stages of tissue repair, shaping an anti-inflammatory immune microenvironment. Metal-polyphenol complexes also have a variety of enzyme activities, which can remove excess reactive oxygen species (ROS) in tissues and improve tissue microenvironment. GelMA is widely used in tissue repair and regeneration because it has the RGD sequence for cell adhesion and the MMP sequence that supports enzymatic hydrolysis. It can also achieve tissue adhesion on the skin surface through hydrogen bonding, π-π stacking, etc.
[0004] Therefore, how to design and prepare hydrogel dressings using metals, polyphenols and GelMA so that they can simultaneously achieve multiple functions and biological activities will be of great significance and application value in promoting the repair of complex wounds such as infectious diabetic wounds. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an injectable self-healing hydrogel dressing. The prepared hydrogel dressing has good tissue adhesion, hemostasis function and multiple biological functions, and can effectively promote the healing of diabetic wounds.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing an injectable self-healing hydrogel dressing, the method comprising the following steps:
[0008] (1) mixing copper chloride dihydrate CuCl2·2H2O and protocatechuic aldehyde PA in deionized water and adjusting the pH to an alkaline environment to obtain a first solution containing a copper protocatechuic aldehyde complex CuPA;
[0009] (2) dissolving methacrylated gelatin GelMA and an initiator in a buffer solution to prepare a second solution;
[0010] (3) adding the first solution into the second solution and mixing them evenly, and then photocuring and cross-linking to form an injectable self-healing hydrogel dressing.
[0011] The technical concept of the present invention is that copper chloride dihydrate and protocatechuic aldehyde form a copper-protocatechuic aldehyde complex CuPA with active oxygen scavenging properties under weak alkaline conditions (pH 8.7). The aldehyde group in the copper-protocatechuic aldehyde complex forms a dynamic Schiff base bond with the amino group on GelMA, and the methacryloyl bond in GelMA polymerizes and crosslinks under the initiator and ultraviolet light. The hydrogel is given injectable self-healing properties through a double cross-linked network, and the dynamic Schiff base bond can respond to the acidic microenvironment to achieve sustained release of CuPA. The CuPA complex simultaneously has multiple biological activities such as antibacterial, anti-inflammatory, antioxidant, and angiogenesis, and can promote the repair of infectious diabetic wounds.
[0012] In step (1), the pH is less than 9.0.
[0013] Preferably, in step (1), the preparation method of the copper-protocatechuic aldehyde nanocomposite (CuPA) is as follows: dissolving cupric chloride dihydrate (CuCl2·2H2O) and protocatechuic aldehyde (PA) in deionized water, adjusting the pH of the mixed solution to 8.7 with sodium hydroxide solution, and stirring the mixture at room temperature for 3 hours to obtain the copper-protocatechuic aldehyde complex (CuPA).
[0014] Since protocatechuic aldehyde contains catechol and aldehyde structures, it will undergo varying degrees of oxidation in an alkaline environment, under oxidants, and under ultraviolet light to form a quinone structure. Therefore, the reaction conditions of CuPA need to be reasonably controlled. The concentration ratio of copper ions to PA should be controlled at 1:2, and the pH of the alkaline environment should not be higher than 9.0. The entire reaction must be strictly protected from light to prevent PA from being oxidized under light, which would affect the formation of the CuPA complex and the antioxidant activity of the formed CuPA.
[0015] In step (2), the preparation method of the methacrylated gelatin GelMA is as follows: adding pig skin gelatin to a buffer solution and stirring to dissolve, then adding methacrylic anhydride solution dropwise and stirring to react, adding a buffer solution to terminate the reaction to obtain a product solution, and then dialyzing the product solution in deionized water using a dialysis bag with a molecular weight cutoff of 8-14KD, filtering the solution and freeze-drying it to obtain methacrylated gelatin GelMA.
[0016] Preferably, 10% w / v pig skin gelatin (such as Type A, ~300g bloom) is added to a PBS solution, the mixture solution is magnetically stirred at 45-55°C until the gelatin is fully dissolved, then 8-12mL of methacrylic anhydride solution is added dropwise, and the reaction is stirred at 50°C for 3 hours; a PBS solution of 50°C and an equal volume to the above mixed solution is added to terminate the reaction, the resulting product solution is dialyzed in deionized water for 5-7 days using a dialysis bag with a molecular weight cutoff of 8-14KD, the solution is filtered and freeze-dried to obtain methacrylated gelatin GelMA.
[0017] Preferably, in step (2), the initiator is lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP).
[0018] In step (3), the concentration of Cu in the first solution is 0.05M, the concentration of methacrylated gelatin GelMA in the second solution is 5-10%, and the concentration of the initiator is 0.1-0.5%, wherein the percentages are by mass; the volume of the first solution added is 10-20% of the second solution.
[0019] In step (3), the wavelength of the ultraviolet light source used for photocuring is 300-400nm, and the photocuring time is usually 3-5min.
[0020] The present invention also provides an injectable self-healing hydrogel dressing obtained according to the preparation method.
[0021] The present invention also provides an application of the above-mentioned injectable self-healing hydrogel in preparing a diabetic infection wound dressing. Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The injectable self-healing hydrogel dressing prepared by this method has good injectability, self-healing property and tissue adhesion: injectability can not only make the dressing adapt to irregular wound surface, but also facilitate the control of dressing usage and achieve on-demand medication; self-healing property enables the hydrogel dressing to recover to its original state after being damaged by external force; tissue adhesion enables the hydrogel dressing to maintain good adhesion with the tissue interface, thus providing a guarantee for the realization of the effect of the hydrogel dressing in promoting the repair of damaged tissue;
[0023] 2. The injectable self-healing hydrogel dressing prepared by this method has excellent hemostatic properties: the porous hydrogel excipient can quickly absorb platelets from the blood and form a gel-like substance, thereby forming a pressure barrier and promoting blood coagulation; the catechol group in the copper-protocatechuic aldehyde complex CuPA works synergistically with the methacryloyl gelatin GelMA to recruit calcium ions to vascular smooth muscle cells, promote vascular contraction, and thus promote hemostasis;
[0024] 3. The injectable hydrogel dressing prepared by this method is formed by free radical polymerization of the propylene group in methacryloyl gelatin GelMA and cross-linking of dynamic Schiff base bonds formed by the aldehyde group in the copper-protocatechuic aldehyde complex CuPA and the amino group in methacryloyl gelatin GelMA. The pH responsiveness of the Schiff base bond is used to achieve the sustained release of CuPA, while achieving multiple biological functions such as antibacterial, antioxidant, anti-inflammatory, and angiogenesis-promoting.
[0025] Therefore, the present invention uses metal copper ions, protocatechuic aldehyde and methacryloyl gelatin as raw materials, and prepares an injectable self-healing hydrogel dressing with good tissue adhesion and hemostasis function through free radical-initiated polymerization reaction and dynamic Schiff base bond. The low pH responsiveness of Schiff base bond is utilized to release copper-protocatechuic aldehyde complex CuPA to exert its multiple functions and biological activities such as antibacterial, antioxidant, anti-inflammatory, and angiogenesis promotion, thereby improving the tissue microenvironment of infectious diabetic wounds and promoting the healing of diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 AI in the figure is the transmission electron microscope image (scale bar: 200 nm), element distribution map (scale bar: 100 nm), Fourier transform infrared spectrum (FTIR), Raman spectrum (Raman), X-ray photoelectron spectroscopy (XPS) and other material characterizations of the copper-protocatechuic aldehyde complex CuPA in Example 1, as well as the antioxidant property determination of CuPA;
[0027] Figure 2AI in it is the transmission electron microscope image (scale: 5 nm), element distribution map (scale: 100 nm), Fourier transform infrared spectrum (FTIR), X-ray diffraction spectrum (XRD), X-ray photoelectron spectroscopy (XPS) and other material characterizations of the ceria nanozyme Ce NPs in Comparative Example 2, as well as the antioxidant property determination of the ceria nanozyme Ce NPs;
[0028] Figure 3 AF in the figure are scanning electron microscope images, pore analysis, element distribution maps, Fourier transform infrared spectra (FTIR) and other material characteristics of three hydrogel dressings of GCP of Example 2, GelMA of Comparative Example 1 and GC of Comparative Example 2. Figure 3 GK in the figure is the injectability, self-healing, tissue adhesion and other properties of the GCP hydrogel dressing prepared in Example 2;
[0029] Figure 4 AE in the above is the determination of the hemostasis, hemolysis, swelling and other properties of the GCP hydrogel dressing in Application Example 1. Figure 4 FK in the figure is the antioxidant property test of three hydrogel dressings: GelMA of Comparative Example 1, GC of Comparative Example 2 and GCP of Example 2.
[0030] Figure 5 AD in the figure is the cell compatibility test of the GCP hydrogel dressing in Application Example 3. Figure 5 EF in is the intracellular active oxygen scavenging property of the GCP hydrogel dressing in Application Example 2;
[0031] Figure 6 AK in the figure is the determination of the cell migration promoting, anti-inflammatory and angiogenesis promoting functions of different hydrogel dressings in Application Example 3;
[0032] Figure 7 AF in it are the test results of the antibacterial properties of different hydrogel dressings in Application Example 4;
[0033] Figure 8 The AI in is the efficacy determination of different hydrogel dressings in Application Example 5 in promoting the repair of infectious diabetic wounds. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] Under nitrogen protection, 0.14 g PA was fully dissolved in 5 mL of 80°C deionized water (0.2 M), and then 5 mL of 0.1 M CuCl2·2H2O solution was added to the PA solution. Then, the pH of the mixture was adjusted to 8.7 with sodium hydroxide solution (1 M). After stirring at 600 rpm for 3 h in the dark, the copper-protocatechuic aldehyde complex CuPA was obtained.
[0037] like Figure 1 As shown in Figure 2, TEM and EDS results show that CuPA is a typical nanosheet structure, and the Cu element is evenly distributed in it ( Figure 1 AB in the FTIR spectrum of protocatechuic aldehyde (PA) ( Figure 1 C), 3230cm -1 and 1298cm -1 The stretching vibrations of the OH bond and CO bond of the phenolic hydroxyl group are 1597 cm -1 and 1447cm -1 Belongs to the skeleton vibration of benzene ring, 1872cm -1 、1754cm -1 、877cm -1 and 811cm -1 This indicates that 1, 2, 4 tri-substitution has occurred on the benzene ring, 2820 cm -1 and 2749cm -1 The C=O bond of the aldehyde group is directly connected to the benzene ring and conjugated, so its wave number moves to a low frequency of 1652 cm -1 After the introduction of Cu, the overall peak intensity weakened and moved to high frequency, which may be related to the formation of hydrogen bonds and changes in molecular structure. The Raman spectrum of PA is 300-2000cm -1 The following characteristic peaks appear in the spectrum: 813cm -1 and 1597cm -1 Belongs to the strong stretching vibration of the benzene ring, 1165cm -1 The main vibration modes include the CH bond vibration connected to the benzene ring and some OH bond shear vibration. -1 The main vibration modes are benzene ring stretching and some OH bond shear vibrations. -1 It can be attributed to the HC=O shear vibration and part of the OH shear vibration, 1647cm -1 It is attributed to the CC=O stretching vibration connected to the benzene ring. After adding copper chloride, at 432cm -1A small peak appears, which can be attributed to the typical Raman vibration of the copper chloride molecule. In addition, the addition of copper chloride causes a certain degree of change in the overall system, which in turn causes a certain degree of displacement of the Raman characteristic peaks on the CuPA Raman spectrum, which is manifested as the movement of the characteristic peaks belonging to PA, such as the benzene ring vibration peak at 813cm -1 and 1597cm -1 The wavelengths of the spectral shifts are 15 and 22 wavenumbers to 798 cm -1 and 1575cm -1 The disappearance of some peaks may be due to the insufficient intensity of the original peaks, which are covered by the new background ( Figure 1 D). Figure 1 In Figure E, the XPS peaks of CuPA show that Cu 2+ The proportion is as high as 91.71%, Cu + The percentage of CuPA in the ion exchange rate was 8.29%, indicating that the valence state of copper ions in CuPA was mainly +2, which also indicated that the CuPA complex was successfully synthesized. The ability of CuPA to remove ROS was investigated using an antioxidant kit. The results showed that CuPA had a strong inhibitory effect on the ROS removal in the range of 5-100 μg mL -1 It has good superoxide anion scavenging ability within the concentration range ( Figure 1 F and H), at 1-5 μg mL -1 It also exhibits good DPPH scavenging ability within the concentration range ( Figure 1 G and I). Among them, *p<0.05, **p<0.01, ***p<0.001.
[0038] Example 2
[0039] Preparation of injectable self-healing hydrogel excipient GCP:
[0040] (1) Preparation of GelMA: 10% w / v pig skin gelatin was added to PBS solution, and the mixture solution was magnetically stirred at 45-55°C until the gelatin was fully dissolved, and then 8-12 mL of methacrylic anhydride solution was added dropwise, and stirred at 50°C for 3 hours. A 50°C PBS solution of equal volume to the above mixed solution was added to terminate the reaction, and the obtained product solution was dialyzed in deionized water for 5-7 days using a dialysis bag with a molecular weight cutoff of 8-14KD, and then the solution was filtered and freeze-dried to obtain methacrylated gelatin GelMA;
[0041] (2) A copper-protocatechuic aldehyde complex CuPA solution was prepared according to Example 1, wherein the concentration of Cu was 0.05 M;
[0042] (3) 0.5 g of GelMA and 0.0125 g of photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) were dissolved in 5 mL of PBS (i.e., 10% GelMA and 0.25% LAP), and heated and stirred to dissolve. The mixture was then thoroughly mixed with the CuPA solution at a volume ratio of 9:1, and irradiated under 395 nm ultraviolet light for 3 min to form a GCP hydrogel.
[0043] Comparative Example 1
[0044] Preparation of light-cured GelMA hydrogel dressing: 0.5 g GelMA and 0.0125 g photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP) were dissolved in 5 mL PBS (i.e., 10% GelMA and 0.25% LAP). The mixture was thoroughly mixed with PBS solution at a volume ratio of 9:1, and irradiated under 395 nm ultraviolet light for 3 min to form GelMA hydrogel.
[0045] Comparative Example 2
[0046] Preparation of light-cured GC hydrogel dressing:
[0047] (1) Preparation of ceria nanozyme Ce NPs: 0.43 g cerium acetate and 3.25 g oleylamine were thoroughly mixed with 15 mL xylene and stirred at room temperature for 24 h. The solution was heated to 90 °C under vacuum conditions, 1 mL of deionized water was added, and aged at 90 °C for 3 h. Then, Ce NPs were precipitated with ethanol, centrifuged and washed with acetone, and the obtained Ce NPs were dispersed in chloroform and precipitated with mPEG. 2k -DSPE was used to transfer Ce NPs into the aqueous phase and prepared into 5 mg mL -1 Aqueous solution.
[0048] (2) 0.5 g of GelMA, 0.0125 g of photoinitiator lithium phenyl-2,4,6-trimethylbenzoylphosphinate (LAP), and 0.3 mL of Ce NPs solution (5 mg mL -1 ) was dissolved in 4.7 mL of PBS and irradiated under 395 nm UV light for 3 min to form GC hydrogel.
[0049] Figure 2 AI in it is the material characterizations such as transmission electron microscopy (scale: 5 nm), element distribution map (scale: 100 nm), Fourier transform infrared spectrum (FTIR), X-ray diffraction spectrum (XRD), X-ray photoelectron spectrum (XPS) of the ceria nanozyme Ce NPs in Comparative Example 2, as well as the antioxidant property determination of ceria nanozyme Ce NPs. Figure 2The AB in the figure shows the successful preparation of ceria nanozyme Ce NPs, which has a diameter of about 3nm and a lattice spacing of ~0.32nm. Elemental mapping analysis confirms the uniform distribution of Ce elements in Ce NPs. FTIR spectrum ( Figure 2 C) The Ce-O bond in Ce NPs was observed at 472 cm -1 The stretching vibration at the XRD characterization results ( Figure 2 D), Ce NPs present a cubic fluorite structure, and obvious (111), (200), (220), (311), (400) and (331) crystal plane diffraction peaks can be observed. 3+ Accounting for 42.85% of CeNPs, Ce 4+ accounted for 57.15%, which indicates that Ce NPs are composed of Ce 4+ and Ce 3+ The mixed valence composition of the valence ratio is about 1.3 ( Figure 2 E). Figure 2 In 2F-I, Ce NPs exhibited strong antioxidant capacity by effectively scavenging reactive oxygen species such as superoxide anions and DPPH: Figure 2 The F and H in the Ce NPs were in the range of 1-100 μg mL -1 Superoxide anion scavenging capacity within a range of concentrations; Figure 2 The G and I in the samples were Ce NPs in the range of 1-100 μg mL -1 The scavenging ability of DPPH within the concentration range. *p<0.05, **p<0.01, ***p<0.001.
[0050] Figure 3 AF in the figure are scanning electron microscope images, pore analysis, element distribution map, Fourier transform infrared spectrum (FTIR) and other material characteristics of three hydrogel dressings of GCP in Example 2, GelMA in Comparative Example 1 and GC in Comparative Example 2. Scanning electron microscope (SEM) and element analysis showed that GelMA, GC and GCP hydrogels all had porous network structures, and there was no significant difference in pore size between the groups ( Figure 3 The copper element in the GCP hydrogel and the cerium element in the GC hydrogel are evenly distributed throughout the hydrogel network ( Figure 3 in the CD). Figure 3 E in the figure is the transformation process of GelMA, GC and GCP hydrogels from liquid to solid under ultraviolet irradiation. Figure 3 F), gelatin at 2500-3300cm -1 and 3200-3700cm -1The prominent broad peaks in the range should be attributed to the stretching vibration of OH related to carboxyl and hydroxyl groups, which are the characteristic peaks of gelatin. Gelatin, GelMA and GCP have peaks at 3423 and 3077 cm -1 The peak at 1647 cm indicates the stretching vibration of the NH bond. -1 The peak at 1540 cm represents the stretching vibration of the C=O bond, while the peak at 1540 cm -1 The peaks at represent the stretching vibration of the CN bond and the bending vibration of the NH bond. Compared with gelatin, the addition of MA reduces the absorption peak intensity of GelMA. This reduction is mainly due to the acylation reaction between the carbonyl group on MA and the hydroxyl group on gelatin, which significantly weakens the absorption peak related to OH stretching vibration. The absorption peak intensity of GCP hydrogel is lower than that of GelMA, which may be the result of the change of GelMA molecular structure caused by CuPA complex.
[0051] Application Example 1
[0052] Determination of injectable, self-healing, tissue adhesion and hemostatic properties of injectable self-healing hydrogel dressing GCP:
[0053] Figure 3 GK in the figure is the GCP prepared in Example 2. Determination of the injectability, self-healing, tissue adhesion and other properties of the hydrogel dressing:
[0054] Figure 3 In the G in the shear thinning experiment, the viscosity of GCP dressing is logarithmically related to the shear rate, and the viscosity gradually decreases with the increase of shear rate, indicating that GCP has good shear thinning properties. The modulus test of GCP was carried out by rheometer ( Figure 3 H) and structural recovery experiments ( Figure 3 The self-healing properties of hydrogel GCP were evaluated by using the I in Figure 1. When the frequency remained constant at 1 Hz and the strain reached 294.7%, the loss modulus (G”) was greater than the storage modulus (G’), and the hydrogel mainly underwent viscous deformation, changing from solid to liquid ( Figure 3 H in the figure). When the strain is 5%, the storage modulus is greater than the loss modulus, and the hydrogel is solid. When the strain is adjusted to 500%, the loss modulus is greater than the storage modulus, and the hydrogel becomes liquid. The material changes from elastic deformation to viscous deformation. After three reciprocating cycles, GCP alternates between solid and liquid states, and the storage modulus and loss modulus remain basically the same, which shows that GCP hydrogel has good self-healing function ( Figure 3 I in. Figure 3The J in Figure 1 also showed that the GCP hydrogel had significant self-healing properties. The whole process mainly involved the breaking and reversible recombination of Schiff base bonds and copper-catechol coordination bonds. Subsequently, biological tissues of C57BL / 6 mice were used to evaluate the tissue adhesion properties of GCP hydrogels. The results showed that GCP had good adhesion properties and could effectively adhere to the heart, liver, spleen, and kidney tissues of mice ( Figure 3 in K).
[0055] Figure 4 In the AB of the study, a liver injury model was established using 6-week-old SD rats to evaluate the hemostatic effects of different hydrogel dressings within 1 minute ( Figure 4 The results showed that GelMA, GC, and GCP hydrogels exhibited different degrees of hemostatic effects; notably, GCP hydrogel treatment significantly reduced bleeding to 60.53±10.60 mg ( Figure 4 C). Figure 4 D in the figure is the comparison of swelling properties of GelMA, GC and GCP hydrogels. Figure 4 In (E), the GelMA hydrogel was 0.36% ± 0.18%, the GC hydrogel was 0.20% ± 0.09%, and the GCP hydrogel was 0.87% ± 0.09%, all of which were less than the biosafety threshold of 5%.
[0056] Application Example 2
[0057] Determination of the Reactive Oxygen Species Scavenging Properties of Injectable Self-Healing Hydrogel Dressing GCP:
[0058] Figure 4 The antioxidant properties of the three hydrogel dressings were determined by using an antioxidant kit and mouse fibroblasts (L929). The results showed that GCP and GC hydrogels had obvious scavenging effects on·O2 - and DPPH free radicals, GCP hydrogel also has significant catalase-like activity ( Figure 4 FK in: Figure 4 F and I in the figure are the determination of superoxide anion scavenging ability of three hydrogel dressings, GelMA, GC, and GCP; Figure 4 G and J in the figure are the determination of the scavenging ability of three hydrogel dressings, GelMA, GC, and GCP, on DPPH; Figure 4 H and K in the figure are the catalase-like activity determinations of three hydrogel dressings: GelMA, GC, and GCP; *p<0.05, **p<0.01, ***p<0.001).
[0059] After L929 cells were treated with 200 μM hydrogen peroxide (H2O2) and different hydrogels, both GCP and GC hydrogels showed excellent efficacy in scavenging ROS in cells ( Figure 5 E and F in Figure 1: F is the average fluorescence intensity analysis of ROS among the groups in Figure 1, *p<0.05, **p<0.01, ***p<0.001). Compared with GC, GCP hydrogel showed stronger ROS scavenging ability.
[0060] Application Example 3
[0061] Determination of biocompatibility, anti-inflammatory and angiogenic activity of injectable self-healing hydrogel dressing GCP:
[0062] The biocompatibility of GCP hydrogels was evaluated using mouse fibroblasts L929 and human immortalized keratinocytes HaCaT. CCK8 detection and Calcein / PI staining showed that ( Figure 5 AD in: Figure 5 A and B in the figure show the cell viability and Calcein / PI staining of L929 cells cultured for 12 and 24 hours, respectively (scale bar: 200 μm); Figure 5 C and D in the figure show the cell viability and Calcein / PI staining of HaCaT cells after hydrogel treatment for 12 and 24 hours, respectively (scale bar: 200 μm); Figure 5 Figure E is a fluorescence image of ROS measurement in L929 cells after treatment with different hydrogel dressings (scale: 200 μm). After 12 and 24 hours of treatment with different hydrogel dressings, the survival rates of L929 and HaCaT cells exceeded 95%, and no obvious signs of cell death were observed. These results indicate that GelMA, GC, and GCP hydrogels have good cell compatibility.
[0063] Subsequently, the present invention further studied the ability of hydrogel to promote L929 cell migration. When the hydrogel was co-cultured with L929 cells, GCP hydrogel could significantly accelerate the migration of L929 cells within 24 hours compared with the control group, GelMA group and GC group ( Figure 6 A and B in the figure: Cell migration and migration distance analysis of L929 cells after being treated with different hydrogel dressings for 24 hours (scale: 200 μm). ), indicating that GCP hydrogel has a strong ability to promote fibroblast migration.
[0064] In diabetic patients, high blood sugar levels trigger a series of inflammatory responses, promoting the body to produce various inflammatory mediators, such as iNOS, IL-1β and TNF-α. The continuous release of these factors may lead to chronic inflammation and immune dysfunction. -1The anti-inflammatory properties of the hydrogel materials were detected by co-culturing mouse mononuclear macrophages (RAW264.7) with LPS. Real-time fluorescence quantitative PCR (qRT-PCR) and Western blotting data showed that GC and GCP hydrogels could significantly reduce the mRNA and protein expression levels of iNOS, IL-1β and IL-6 in RAW264.7 cells ( Figure 6 CI in: Figure 6 CE in the figure is the relative expression of iNOS, IL-1β, and IL-6 mRNA in macrophage Raw264.7 cells after treatment with different hydrogel dressings. Figure 6 F in the figure is the Western blotting diagram of iNOS, IL-1β and IL-6 expression in each treatment group. Figure 6 GI in the figure is the relative protein expression level of iNOS, IL-1β, and IL-6. Figure 6 J in the figure is the relative mRNA expression of VEGF in HUVECs treated with different hydrogel dressings. Figure 6 K in the figure is the VEGF protein concentration in HUVECs after intervention with different hydrogel dressings measured by ELISA kit; *p<0.05, **p<0.01, ***p<0.001). GCP hydrogel showed the most obvious anti-inflammatory effect, which may be attributed to the anti-inflammatory properties of polyphenol compounds.
[0065] Long-term hyperglycemia leads to peripheral circulatory dysfunction, and promoting angiogenesis is beneficial for delivering immune cells, sufficient nutrients and oxygen to the wound site, promoting tissue remodeling and regeneration. The function of hydrogels in promoting angiogenesis was evaluated by co-culturing HUVECs with different hydrogels, extracting RNA and protein from HUVECs, and using qRT-PCR and ELISA kits for detection. The results showed that after GCP intervention, the mRNA and protein expression of VEGF increased ( Figure 6 J and K), demonstrating that GCP has the ability to enhance angiogenesis.
[0066] Application Example 4
[0067] Antimicrobial performance testing of injectable self-healing hydrogel dressing GCP:
[0068] Slow wound healing in diabetes is often associated with bacterial infection, which can trigger an inflammatory response and may cause fluctuations in blood sugar levels in diabetic patients, or even lead to more serious complications such as cellulitis and sepsis. The antibacterial effect of GCP was evaluated by dilution plate spreading, scanning electron microscopy (SEM), and SYTO9 / PI staining. Figure 7 A in the figure is a plate coating image of Staphylococcus aureus and Escherichia coli after being treated with different hydrogel dressings. Figure 7B in the figure is a scanning electron micrograph of Staphylococcus aureus and Escherichia coli after treatment with different hydrogel dressings (scale: 1 μm). Figure 7 C and D are the bacterial activities of Staphylococcus aureus and Escherichia coli after treatment with different hydrogel dressings: Figure 7 Figures A, C, and D show that GCP significantly reduced the bacterial viability of Staphylococcus aureus and Escherichia coli. SEM analysis showed that the inherent morphology of these two bacteria changed significantly, and the original spherical and rod-shaped structures of the bacteria were destroyed, resulting in decreased viability and bacterial death ( Figure 7 B), indicating that GCP hydrogel has a strong antibacterial effect on Staphylococcus aureus and Escherichia coli. SYTO9 / PI staining further confirmed this conclusion. The green fluorescent SYTO9 marked the bacterial cell membrane, while PI penetrated the damaged membrane to stain the bacterial nucleus and emitted red fluorescence in dead bacteria. SYTO9 can identify both live and non-live bacteria, while PI can only specifically mark dead bacteria. Figure 7 E and F in the figure are SYTO9 / PI staining images of Staphylococcus aureus and Escherichia coli after being treated with different hydrogel dressings (scale bar: 1 mm). The fluorescence staining results show that after being treated with GCP hydrogel, Staphylococcus aureus ( Figure 7 E) and Escherichia coli ( Figure 7 The number of viable bacteria in F) was significantly reduced. Figure 7 Middle: *p<0.05, **p<0.01, ***p<0.001.
[0069] Application Example 5
[0070] Injectable self-healing hydrogel dressing GCP promotes the repair of infectious diabetic wounds:
[0071] Figure 8 A in Figure 1 shows the specific animal experimental protocol. A diabetic rat model was constructed and randomly divided into four groups: control group, GelMA group, GC group, and GCP group. After anesthesia, a 10 mm full-thickness circular wound was made on the back of the rat. At the same time, 10 μL of Staphylococcus aureus (1.0×10 8 CFU mL -1 ) and 100 μL of different cured hydrogels were used to treat the wounds. The day of surgery was designated as day 0. Wound images of each group of diabetic rats were recorded on days 0, 2, 4, 7, 10, and 14, respectively. On days 7 and 14, the wounds of each group were taken for hematoxylin-eosin (H&E) staining and Masson's trichrome staining to evaluate the epidermal thickness, wound length, and collagen density. In addition, the wound sections obtained on day 7 were subjected to immunofluorescence (IF) staining to evaluate the anti-inflammatory and angiogenic abilities of the hydrogel during wound healing. The wound images of rats in each group are shown in Figure 8B in the figure shows representative images of the wounds of rats in each group on days 0, 2, 4, 7, 10, and 14; the wound healing trajectory is shown in Figure 8 Figure C is a fitting diagram of the wound healing area of rats in different hydrogel dressing treatment groups after 14 days (blue: day 0; yellow: day 2; green: day 4; orange: day 7; pink: day 10; red: day 14). The results showed that the wound area of all groups gradually decreased over time, among which GCP hydrogel showed the most significant effect in promoting wound healing. From the second day to the end of the experiment, the wound area of rats in the GC and GCP groups was significantly smaller than that in the control group. In addition, compared with the GC group, the wound area of the GCP group on the 7th and 10th days was significantly reduced ( Figure 8 D, wound area analysis of rats in different hydrogel dressing treatment groups on days 0, 2, 4, 7, 10, and 14). H&E staining and Masson's trichrome staining showed that epithelial gaps and wound widths gradually decreased and collagen density increased on days 7 and 14 after GCP treatment ( Figure 8 EI in: Figure 8 E and F are representative H&E staining and Masson trichrome staining images of wound tissues of rats in different hydrogel dressing treatment groups on the 7th and 14th days, respectively (scale bars: 500 μm and 200 μm); Figure 8 GI in the figure is the analysis of epidermal thickness, wound length, and collagen density of rat wounds in different hydrogel dressing treatment groups; *p<0.05, **p<0.01, ***p<0.001). This indicates that GCP hydrogel can effectively promote the re-epithelialization and collagen fiber formation of diabetic infected wounds, thereby accelerating the healing of infected wounds.
Claims
1. A method for preparing an injectable self-healing hydrogel dressing, characterized in that: The preparation method comprises the following steps: (1) mixing copper chloride dihydrate CuCl2·2H2O and protocatechuic aldehyde PA in deionized water and adjusting the pH to an alkaline environment to obtain a first solution containing a copper protocatechuic aldehyde complex CuPA; (2) dissolving methacrylated gelatin GelMA and an initiator in a buffer solution to prepare a second solution; (3) adding the first solution into the second solution and mixing them evenly, and then photocuring and cross-linking to form an injectable self-healing hydrogel dressing.
2. The method for preparing the injectable self-healing hydrogel dressing according to claim 1, characterized in that: In step (1), the pH is less than 9.
0.
3. The method for preparing the injectable self-healing hydrogel dressing according to claim 1, characterized in that: In step (2), the preparation method of the methacrylated gelatin GelMA is as follows: adding pig skin gelatin to a buffer solution and stirring to dissolve, then adding methacrylic anhydride solution dropwise and stirring to react, adding a buffer solution to terminate the reaction to obtain a product solution, and then dialyzing the product solution in deionized water using a dialysis bag with a molecular weight cutoff of 8-14KD, filtering the solution and freeze-drying it to obtain methacrylated gelatin GelMA.
4. The method for preparing the injectable self-healing hydrogel dressing according to claim 1, characterized in that: In step (3), the concentration of Cu in the first solution is 0.05M, the concentration of methacrylated gelatin GelMA in the second solution is 5-10%, and the concentration of the initiator is 0.1-0.5%, wherein the percentages are by mass; the volume of the first solution added is 10-20% of the second solution.
5. The method for preparing the injectable self-healing hydrogel dressing according to claim 1, characterized in that: In step (3), the wavelength of the ultraviolet light source used for photocuring is 300-400nm, and the photocuring time is usually 3-5min.
6. An injectable self-healing hydrogel dressing obtained according to the preparation method according to any one of claims 1 to 5.
7. Use of the injectable self-healing hydrogel according to claim 6 in preparing a diabetic infected wound dressing.
Citation Information
Patent Citations
Hydrogel dressing loaded with metal-polyphenol functional particles as well as preparation method and application of hydrogel dressing
CN113648454A
Dynamic characteristic adjustable hydrogel as well as preparation method and application thereof
CN114349990A
Double-dynamic cross-linked hydrogel for slowly releasing glehnia littoralis lactone as well as preparation method and application of double-dynamic cross-linked hydrogel
CN116120595A
ADM composite hydrogel as well as preparation method and application thereof
CN117462735A
Antibiotic-metal complexes in the detection of gram-negative bacteria and other biological analytes
WO2001027628A1
Cited By
Traditional Chinese medicine composite hydrogel for repairing diabetic bone defect as well as preparation method and application of traditional Chinese medicine composite hydrogel
CN120392652A